Sonderpädagog*in werden: Auf dem Weg zu einer professionellen Haltung Eine rekonstruktive Studie im Kontext inklusionsorientierter Lehrer*innenbildung - Junge, Alice (Perspektiven sonderpädagogischer Forschung, 2020)
"...we're all wonderful, no matter how different we are as people." Taken from an interview conducted for this dissertation, this statement exemplifies one of the findings of the study: The basic idea of inclusion is often praised in euphoric terms. At the same time, however, it is possible to observe challenges and significant areas of tension regarding its professional implementation. The dissertation is located in the context of research on inclusive teacher education and addresses the question of which aspects of teacher education characterize the development of a professional attitude and what role is played by one's own professional self-image, ideas about disability and the attribution of competencies and performance during this education.To answer this question, students studying special education at the university were interviewed. These students are in a special phase of upheaval which opens professional opportunities for them in both special needs schools and regular schools. The requirements and concrete tasks before them vary considerably depending on their professional location. Uncertainty related to these requirements and tasks, as well as the desire to resolve it, are central to the results of this study and are handled differently by the students surveyed. Using objective hermeneutics, four cases are analysed and interpreted. This reconstructive procedure opens up the possibility of examining statements that are subject to a certain subject-specific social desirability for their latent meaning and thus to arrive at more profound insights into the subject matter of the study. With the help of central theories of professionalism and the theory of Bildung as a transformational process, the results of the study show that existing beliefs and biographically acquired experiences of students guide and influence their educational processes on the way to the development of a professional attitude. Two aspects of special concern in this study were the need for students to be recognized as a ,real' teacher and their awareness that people with disabilities require increased assistance while at the same time denying their extant skills. One further observation made in this study is the disregard for the idea that Bildung, understood as an educational aim that goes beyond mere classroom integration, is also an important educational aim for children with disabilities. They show that statements like the one cited at the beginning of this abstract should be examined for the normative contradictions it may obscure. This leads to several conclusions that are relevant especially for the first phase of teacher training.The dissertation thus employs reconstructive studies in order to illuminate the research field of teacher education and professional attitudes. It will be of interest for providing vivid insights into the application of the method of objective hermeneutics in a field of special and inclusive education.